Resonance Magnetoelectric Effect in NaNbO3–NiFe2O4 Composite. Issue 2 (28th December 2012) - Han, Yemei; Li, Lingxia; Wang, Zhi; Guo, Dong; Zhang, Mingming; Ramesh, R.
<x xml:space="preserve">Abstract</x> Electric field‐induced magnetization characteristics are demonstrated in (100−x)NaNbO3–xNiFe2O4(x = 15, 25, 35, 45), synthesized by the solid‐state sintering method. The composites show well‐defined ferroelectric behaviors and magnetic characteristics. The CME effect characteristics with driving frequency in a range 10 k–15 kHz were investigated at room temperature. The CME couplings increase initially with increasing the driving frequencies and then decrease with the further increase in the frequency. Large CME coefficients are obtained at electromechanical resonance frequency of 12.8 kHz. These lead‐free multiferroic composites exhibiting electrostatically induced ME resonance provide great opportunities for electric field‐tunable microwave devices.